Book Review: Supply Risk Assessment in SCM- Assessing Supply Side Risks - Hafsa Maryam (International Journal of Supply Chain Management, 2013)
Purchasing and supply management are widely acknowledged as strategies for companies. To make a prudent supplier selection decision, it is important to plan for uncertainty to mitigate risk. The study aims to address the risk which originates at the suppliers end. This book focuses on categorization and prioritization of the risk elements and addressing a supplier selection problem with the risk elements under consideration. The increasing complexity of products and services, shorter product life cycles, globalization of trade and the improvement in logistics have led companies to focus on their core business.